The celluloid courtroom : a history of legal cinema - Levi, Ross D., 1967- (Praeger Publishers, 2005)
The genre of legal cinema is an extensive and revealing one: it is a body of films that depicts lawyers, clients, criminals, judges, and juries, often not as they actually are, but as we would like them to be. The idealized courtroom of many legal movies tells us a great deal about what we think of our justice system and what we want it to reflect about America, but the films in the genre vary widely in how they do this. From To Kill a Mockingbird to Liar, Liar, from A Time to Kill to Twelve Angry Men, we see certain stereotypes repeating themselves again and again: the judge as stern referee.